4
$\begingroup$

Simple way to solve this exercise

$$ x = \sqrt[3]{9+\sqrt{80}}+\sqrt[3]{9-\sqrt{80}} $$

$\endgroup$

closed as off-topic by heropup, user147263, graydad, user21820, user99914 Sep 21 '15 at 2:54

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – heropup, graydad, user21820
If this question can be reworded to fit the rules in the help center, please edit the question.

4
$\begingroup$

You are given two nested radicals. To denest each of them, we can try to find two numbers $u,v\in\mathbb {Q} $ such that

\begin{equation*} 9+\sqrt{80}=\left( u+\sqrt{v}\right) ^{3},\qquad 9-\sqrt{80}=\left( u-\sqrt{v }\right) ^{3}.\tag{1} \end{equation*}

The product

\begin{equation*} \left( u+\sqrt{v}\right) \left( u-\sqrt{v}\right) =u^{2}-v=\sqrt[3]{9+\sqrt{ 80}}\sqrt[3]{9-\sqrt{80}}=1 \end{equation*}

implies that

\begin{equation*} v=u^{2}-1, \end{equation*}

and

\begin{equation*} 9+\sqrt{80}=\left( u+\sqrt{u^{2}-1}\right) ^{3}=4u^{3}-3u+\sqrt{\left( u^{2}-1\right) \left( 4u^{2}-1\right) ^{2}}.\tag{2} \end{equation*}

A solution is

\begin{cases} 4u^{3}-3u=9 \\ \left( u^{2}-1\right) \left( 4u^{2}-1\right) ^{2}=80\tag{3} \end{cases}

Since

\begin{eqnarray*} 4u^{3}-3u-9 &=&4\left( u-\frac{3}{2}\right) \left( u^{2}+\frac{3}{2}u+\frac{3 }{2}\right),\\ ( u^{2}-1) ( 4u^{2}-1) ^{2}-80 &=&16u^{6}-24u^{4}+9u^{2}-81 \\ &=&16\left( u+\frac{3}{2}\right) \left( u-\frac{3}{2}\right) \left( u^{2}- \frac{3}{2}u+\frac{3}{2}\right) \left( u^{2}+\frac{3}{2}u+\frac{3}{2}\right) , \end{eqnarray*}

the single solution of $(3)$ is

\begin{equation*} u=\frac{3}{2}.\tag{4} \end{equation*}

Consequently, $v=u^{2}-1=\frac{5}{4}$,

\begin{equation*} 9+\sqrt{80}=\left( \frac{3}{2}+\frac{\sqrt{5}}{2}\right) ^{3},\qquad 9-\sqrt{ 80}=\left( \frac{3}{2}-\frac{\sqrt{5}}{2}\right) ^{3}\tag{5} \end{equation*}

and

\begin{eqnarray*} x &=&\sqrt[3]{9+\sqrt{80}}+\sqrt[3]{9-\sqrt{80}}=\frac{3}{2}+\frac{\sqrt{5}}{2}+\frac{3}{2}-\frac{\sqrt{5}}{2}=3.\tag{6} \end{eqnarray*}

$\endgroup$
10
$\begingroup$

HINT:

$$x^3=9+\sqrt{80}+9-\sqrt{80}+3\sqrt[3]{(9+\sqrt{80})(9-\sqrt{80})}(x)=18+3x$$

$$\iff x^3-3x-18=0$$

of which $x=3$ is a root(by inspection)

Find the other two roots from $$\frac{x^3-3x-18}{x-3}=0$$

$\endgroup$
  • $\begingroup$ "By inspection", using the rational root theorem. $\endgroup$ – Alphonse Dec 23 '16 at 14:24
7
$\begingroup$

Another way: notice that $$\left(\frac{3\pm\sqrt5}{2}\right)^3=9\pm\sqrt{80}.$$

$\endgroup$
4
$\begingroup$

If you know some algebraic number theory, the fact that $(9+\sqrt{80})(9-\sqrt{80})=1$ says that $9\pm\sqrt{80}=9\pm4\sqrt5$ is an even power of the fundamental unit ${1+\sqrt5\over2}$ in $\mathbb{Q}(\sqrt5)$, i.e. a power of $\left({1+\sqrt5\over2}\right)^2={3+\sqrt5\over2}$. It's clear that expanding $(3+\sqrt5)^n$ will give terms that rapidly exceed $36+16\sqrt5$. In fact you can probably eyeball that $n=2$ is too small but $n=4$ is too big, so the answer must be

$$9\pm\sqrt{80}=\left({3\pm\sqrt5\over2}\right)^3$$

as observed in the answer by O.L.

$\endgroup$
3
$\begingroup$

For a hint:

Note that if $a+b+c=0$ then $a^3+b^3+c^3=3abc$ - can you see how to use that here?


To prove, let $a,b,c$ be the roots of $x^3-px^2+qx-r=0$ so that $p=a+b+c; q=ab+bc+ca; r=abc$ then$$a^3-pa^2+qa-r=0$$$$b^3-pb^2+qb-r=0$$$$c^3-pc^2+qc-r=0$$

Add these equations to obtain:$$(a^3+b^3+c^3)-p(a^2+b^2+c^2)+q(a+b+c)-3r$$And substituting and rearranging we get $$(a^3+b^3+c^3)-3abc=(a+b+c)(a^2+b^2+c^2-ab-bc-ca)$$


To follow the comment about solutions to the cubic, examine the equation $$x^3+3px+q=0$$ and set $x=u+v$ then $$(u+v)^3=3uv(u+v)+u^3+v^3$$ //Note that this is $(u+v)^3-u^3-v^3=3(-u)(-v)(u+v)$ - which is another form of the earlier identity used by lab b in his solution//

and this is equivalent to $$x^3-3uvx-u^3-v^3$$

If we set $p=-uv$ and $q=-u^3-v^3$, we have $u^3, v^3$ as roots of $$y^2+qy-p^3=0$$Using the quadratic formula and $x=u+v$ we recover the form of the roots which is originally given.

Here $p=1, q=-18$ and the roots of the quadratic are $$\frac {18\pm\sqrt{324+-4}}{2}=9\pm \sqrt{80}$$

$\endgroup$
  • $\begingroup$ Thanks, Mark, but i can't understand how i can solve it with that $\endgroup$ – ozik.dev Jun 16 '14 at 10:53
  • $\begingroup$ You could try $x=-a$ and the two other components of your initial equation as $b,c$. As this and other answers/comments will show, problems of this kind are closely related to the solution of the general cubic equation. $\endgroup$ – Mark Bennet Jun 16 '14 at 11:02

Not the answer you're looking for? Browse other questions tagged or ask your own question.